1987
DOI: 10.1002/pssb.2221440127
|View full text |Cite
|
Sign up to set email alerts
|

H2 Dissociation in Nickel. A Cluster Model

Abstract: Dedicated t o Prof. Dr. A. SEECER on the occasion of his 60th birthday A cluster formed by 38 Ni atoms and two H atoms is studied by a semiempirical Hartree-Fock (HF) self-consistent-field (SCF) variant based on the INDO (intermediate neglect of differential overlap) approximation. The energy of the system is analyzed as a function of the spatial localization of t h e two H atoms. The energy minimum in the considered part of the singlet-type potential surface corresponds t o a spatial arrangement where the H a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…As referred by Halet et al29 different possible mechanisms to stabilize H–H interaction in solids are possible, all of them inspired by the already mentioned σ‐back donation bonding. Vargas et al30 have investigated the H occupancy on interstitial sites of fcc Nickel in the diluted solution limit. They found that the double hydrogen occupation of an octahedral site leads to a metastable geometry, where the H–H distance is around 0.85 Å and appear 1 eV/H above the (stable) single occupation case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As referred by Halet et al29 different possible mechanisms to stabilize H–H interaction in solids are possible, all of them inspired by the already mentioned σ‐back donation bonding. Vargas et al30 have investigated the H occupancy on interstitial sites of fcc Nickel in the diluted solution limit. They found that the double hydrogen occupation of an octahedral site leads to a metastable geometry, where the H–H distance is around 0.85 Å and appear 1 eV/H above the (stable) single occupation case.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the density charge in the solid state exhibits the presence of a CP between hydrogen atoms. This particular H–H interaction cannot be rationalized in terms of the standard σ‐back donation mechanism24, 25 and neither does it correspond to a simple dimerization as it has been discussed in hydrogen diluted phases29, 30 or a dihydrogen bond scheme 23, 31, 33. The Westlake's criteria are not followed in this case owing to the particular low dimensionality of the H arrangement in the NiH 2 units.…”
Section: Discussionmentioning
confidence: 96%
“…This secondary minimum is computed to lie only 1 eV above the lowest energy minimum, which corresponds to a spatial arrangement where the H atoms occupy different octahedral sites. 13 In this case, the small size of the cavity is a consequence of the short metal-metal separation. Analogous results obtained in calculations on the Li10H2 edge-sharing bioctahedral cluster might have the same origin.30 Although various theoretical studies of through-space H-H interaction in Pd point to repulsive interactions,14 when the two H atoms were forced to lie inside the same octahedral vacancy, an H-H equilibrium distance of ~0.9 A was calculated,14® a value close to the one found in the above-mentioned13 calculations on nickel hydride.…”
Section: Pairingmentioning
confidence: 99%